Life Satisfaction in Adolescents: A Systematic Literature Review - Erdian, Ayi; Hidayat, Dede Rahmat (Department of Guidance and Counseling, FIP, Undiksha, 2024)
This review reports a systematic literacy review of articles that specifically address life satisfaction experienced by adolescents. Life satisfaction is a cognitive assessment of a person who compares his current state with a state that is considered an ideal state. Changes that occur during adolescence are influenced by factors that contribute to achieving life satisfaction. These contributing factors will be explored further in this study. This systematic literacy study aims to get an overview of what external factors contribute to life satisfaction in adolescents. The method used in this study is a systematic literature review by utilizing two international databases, namely PubMed and Google Scholar. Selection of articles to be analyzed for review using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines with the provision of articles published within the last 5 years (2018-2023). Based on the analysis of the selected articles, it was found that the factors that contribute to life satisfaction in adolescents are social support, with support from family being the main factor, followed by support from friends, and finally support from school. With this, it can also be said that there is a relationship between types of social support, in other words, the perse.